EXPLORING TEXT-IMAGE RELATIONS IN ENGLISH COMICS FOR CHILDREN: THE CASE OF “LITTLE RED RIDING HOOD” - My Nhat, Ton Nu; Mi Pha, Nguyen Thi (VNU Journal of Foreign Studies, 2019)
The present panorama of communication features the co-employment of language and other semiotic resources. This paper addresses this fledging field, multimodal discourse analysis, by investigating a genre targeted at children. Specifically, it studies how meanings in comics for children are constructed both verbally and visually. The data for the study is one comic - Little Red Riding Hood, which is presented via colored images and verbal texts in English . The analysis was based on Unsworth’s (2006) framework to explore the interplay of the two semiotics in the construction of the ideational contents. The results reveal that this comic displays both Expansion and Projection relations with nearly equal occurrence frequencies; however, within each type, the subtypes are vastly different with Verbal being the most predominant, which can be deemed as one of the typical features of the genre in focus. Regarding Expansion, Concurrence and Complementarity have nearly the same high percentage while Enhancement has a lower proportion. Theoretically, the findings concerning a complete full-length comic contribute to the literature on multimodal texts for young learners. The findings also have practical implications for the teaching and learning of English as a foreign language as to how to exploit the free online kid-targeted multimodal resources to engage the young learners in literary works in general and to develop their English proficiency in particular.